Proyecto de prefactibilidad para la creación de una empresa de producción y comercialización de Chicha de Jora en la Parroquia Urbana del Cantón Saraguro de la Provincia de Loja - Saca Macas, Nelly Sara (2023)
“Chicha de jora” is a corn-based drink, very traditional in Saraguro canton, this business idea must be given life through a venture that provides the citizenship with a quality drink, but before placing the money it is necessary to implement the studies carried out and make an instrument that guarantees that the idea is good and that guarantees market and profitability. The main objective is to determine the pre-feasibility for the creation of a company for the production and commercialization of chicha de jora in the urban parish of the Saraguro canton in the province of Loja. A research with a quantitative approach of exploratory and simple descriptive type was carried out with a sample of 353 surveys, directed to people of legal age, an unsatisfied demand of 85,481 liters of chicha de jora was determined, and a commercial plan to introduce the new product was elaborated. The annual capacity used will be 52,000 liters of chicha de jora, which will be constant for the 5 years of its useful life and will have a market share of 60.83%. The company will be incorporated as a limited liability company, and the organizational design has been prepared. The required investment amounts to US$30,213.84, 17.26% of which will be financed by the company itself and 82.74% by a bank loan. The financial indicators were as follows: NPV $81,197.95; IRR 99.31 %; RBC is $0.61 cents for each dollar invested; PRC indicates that it will be recovered in 1 year and 2 months; the sensitivity analysis with the increase in costs can support 31.54 % and with the decrease in income 19.48 % so the project is not sensitive to these percentages to generate profitability. It is concluded that the project is feasible, which indicates that it is an innovative investment alternative that produces profitability.